2015
DOI: 10.1111/ajt.13394
|View full text |Cite
|
Sign up to set email alerts
|

Innate Lymphoid Cells in Graft-Versus-Host Disease

Abstract: Innate lymphoid cells (ILC) are lymphocytes lacking rearranged antigen receptors such as those expressed by T and B cells. ILC are important effector and regulatory cells of the innate immune system, controlling lymphoid organogenesis, tissue inflammation, and homeostasis. The family of ILC consists of cytotoxic NK cells and the more recently described noncytotoxic group 1, 2, and 3 ILC. The classification of noncytotoxic ILC—in many aspects—mirrors that of T helper cells, which is based on the expression of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Allogeneic donor‐derived T cells attacking host epithelial cells cause intestinal barrier loss, which is aggravated by radiotherapy and chemotherapy given in parallel to the transplantation. Subsequent translocation of intestinal bacteria leads to inflammation and activation of the donor immune system . Interestingly, ILC3 seem to play a protective role, since higher numbers of ILC3 in the circulation correlated with a lowered frequency of GvHD in AML patients .…”
Section: Ilc As Guardians Of Tissue Homeostasis Epithelial Remodelinmentioning
confidence: 99%
“…Allogeneic donor‐derived T cells attacking host epithelial cells cause intestinal barrier loss, which is aggravated by radiotherapy and chemotherapy given in parallel to the transplantation. Subsequent translocation of intestinal bacteria leads to inflammation and activation of the donor immune system . Interestingly, ILC3 seem to play a protective role, since higher numbers of ILC3 in the circulation correlated with a lowered frequency of GvHD in AML patients .…”
Section: Ilc As Guardians Of Tissue Homeostasis Epithelial Remodelinmentioning
confidence: 99%
“…The lineage marker-negative innate lymphoid cells (ILCs) are a recently identified family of lymphoid cells that are preferentially located at barrier surfaces and can rapidly secrete immunoregulatory cytokines that correspond to the T H 1, T H 2, or T H 17/T H 22 immune response ( 97 , 98 ). Their role in allogeneic HSCT is gradually being elucidated and it has been recently shown that recipient-derived intestinal ILCs are important in mediating protection from gut GVHD ( 99 , 100 ). However, the nature and role of donor-derived ILC reconstitution remains largely unknown at present ( 101 ).…”
Section: Innate Lymphoid Cellsmentioning
confidence: 99%
“…In this context, it is recently shown that gamma irradiation used in conditioning regimen before HSCT may exert a long-lasting effect on secondary lymphoid organ structure and function ( 40 ). Also, ILC2 appear to be involved in epithelial tissue repair, particularly in lung tissues; however, no data are available to support an actual protection exerted by these cells in GvHD-induced tissue damages ( 42 ).…”
Section: Introductionmentioning
confidence: 99%